Activation of TLR Signaling in Sensitization-Recruited Inflammatory Monocytes Attenuates OVA-Induced Allergic Asthma - Huang, Chao; Wang, Jian; Zheng, Xiaodong; Chen, Yongyan; Wei, Haiming; Sun, Rui; Tian, Zhigang (Frontiers in Immunology, 2018)
The activation of Toll-like receptor (TLR) signaling is widely reported to be involved in preventing the development of allergic asthma. However, the mechanism of the protective function of TLR signaling remains limited. Here, we studied the mouse model of ovalbumin (OVA)-induced allergic asthma and found that deficiency of TLR signaling or activating TLR signaling with agonist would aggravate or attenuate OVA-induced allergic asthma, respectively, and TLR signaling-mediated protective effect mainly affected the sensitization phase. After OVA/alum sensitization, neutrophils and inflammatory monocytes were recruited into peritoneal cavity and up-regulated TLRs expression. However, adoptive transfer of inflammatory monocytes but not peritoneal macrophages or neutrophils induced allergic symptoms in recipient mice after OVA challenge even without OVA/alum sensitization, and treating the inflammatory monocytes with TLR agonist in vitro before transfer could abolish this effect, indicating that recruited inflammatory monocyte played a determinant role in OVA-induced allergic asthma, and activation of TLR signaling in it could attenuate allergic symptoms. Finally, we found that activation of TLR signaling could increase the expression of T-helper (Th) 1-associated cytokines in inflammatory monocytes. Our results suggest that activation of TLR signaling in sensitization-recruited inflammatory monocyte attenuates OVA-induced allergic asthma by promoting the expression of Th1-associated cytokines.